2005
DOI: 10.1103/physrevb.72.174411
|View full text |Cite
|
Sign up to set email alerts
|

Global properties of the spectrum of the Haldane-Shastry spin chain

Abstract: We introduce four types of SU(2M + 1) spin chains which can be regarded as the BC N versions of the celebrated Haldane-Shastry chain. These chains depend on two free parameters and, unlike the original Haldane-Shastry chain, their sites need not be equally spaced. We prove that all four chains are solvable by deriving an exact expression for their partition function using Polychronakos's "freezing trick". From this expression we deduce several properties of the spectrum, and advance a number of conjectures tha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
153
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(154 citation statements)
references
References 45 publications
(84 reference statements)
1
153
0
Order By: Relevance
“…The above defined ordering is effectively a partial ordering, since it does not induce an ordering between ξ p and ξ p ′ whenp =p ′ . It can be shown that the action of H (3.4) on the state vector ξ p yields [7,9] …”
Section: Spectrum Of Spin Cs Modelmentioning
confidence: 99%
See 4 more Smart Citations
“…The above defined ordering is effectively a partial ordering, since it does not induce an ordering between ξ p and ξ p ′ whenp =p ′ . It can be shown that the action of H (3.4) on the state vector ξ p yields [7,9] …”
Section: Spectrum Of Spin Cs Modelmentioning
confidence: 99%
“…To execute this programme, let us first briefly recapitulate the calculation for the partition function of spinless CS model (2.12) at a → ∞ limit [9]. It should be noted that, the eigenvalues in eqn.…”
Section: Partition Function Of Su (M|n) Hs Spin Chainmentioning
confidence: 99%
See 3 more Smart Citations